PREDIKSI KADAR PATI UBI KAYU (Manihot esculenta) PADA BERBAGAI UMUR PANEN MENGGUNAKAN PENETROMETER - Siti Nurdjanah; Susilawati Susilawati; Maya Ratna Sabatini (Jurnal Teknologi & Industri Hasil Pertanian, 2007)
Over the years, determination of starch content by the buyers on the field is performed based on the difference between cassava’s weight on the air and that of in the water, then counted based on the formula designed by International Starch Institute (ISI). This method has been proven to be highly correlated with the starch content determined chemically such as acid hydrolysis. However, this method is less practical due to the need of a large amount of water which is rarely found on cassava plantation. The aims of this study were : 1) to find alternative way to measure cassava’s starch content on the field using penetrometer, 2) to find correlation between starch content measurement using penetrometer and weighing method as described by ISI; correlation between hardness measured using penetrometer and acid hydrolysis. The experiment was arranged as a single treatment harvesting period consisted of 7, 8, 9 and 10 month in a complete randomized  design  with three replications. Data were analyzed using linier regression to find correlation between hardness and starch content analyzed using acid hydrolysis ; correlation between starch yield and starch content analyzed using acid hydrolysis; correlation of starch content analyzed using acid hydrolysis and that of using ISI method. The result shows that there is a high positive correlation between cassava’s hardness using penetrometer and cassava’s starch content using acid hydrolysis method. This implies that penetrometer is a potential tool for predicting cassava’s starch content. Keywords : cassava, penetrometer, hardness, starch content